2015
DOI: 10.1038/nature14864
|View full text |Cite
|
Sign up to set email alerts
|

η-Secretase processing of APP inhibits neuronal activity in the hippocampus

Abstract: Alzheimer disease (AD) is characterized by the accumulation of amyloid plaques, which are predominantly composed of amyloid-β peptide. Two principal physiological pathways either prevent or promote amyloid-β generation from its precursor, β-amyloid precursor protein (APP), in a competitive manner. Although APP processing has been studied in great detail, unknown proteolytic events seem to hinder stoichiometric analyses of APP metabolism in vivo. Here we describe a new physiological APP processing pathway, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
374
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(391 citation statements)
references
References 68 publications
14
374
2
1
Order By: Relevance
“…Overproduced non‐Aβ APP fragments may interact unphysiologically with cellular proteins (Chang & Suh, 2005; Mitani et al , 2012; Nicolas & Hassan, 2014; Kerridge et al , 2015; Nhan et al , 2015; Willem et al , 2015; Xia et al , 2016). See Fig 3.…”
Section: Limitations Of First‐generation Mouse Modelsmentioning
confidence: 99%
“…Overproduced non‐Aβ APP fragments may interact unphysiologically with cellular proteins (Chang & Suh, 2005; Mitani et al , 2012; Nicolas & Hassan, 2014; Kerridge et al , 2015; Nhan et al , 2015; Willem et al , 2015; Xia et al , 2016). See Fig 3.…”
Section: Limitations Of First‐generation Mouse Modelsmentioning
confidence: 99%
“…d-secretase and h-secretase, is just beginning to emerge. 13,14 In healthy brain, non-amyloidogenic and amyloidogenic processing are balanced, with Ab peptides being important effectors in synaptic transmission and plasticity. 15,16 In 2003, Yang et al reported enhanced BACE1-mediated amyloidogenic cleavage in AD.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…Subsequent cleavage by γ-secretase generates Aβ peptide that is believed to play a seminal role in AD pathogenesis [2]. In this report, Willem and colleagues investigated APP fragments at approximately 25kDa that ends at the APP C-terminus [1]. They reasoned correctly that these fragments are processed by alternative proteases that cleave APP at a position N-terminal to the β-secretase cleavage site ( Figure 1).…”
Section: Npgmentioning
confidence: 99%
“…It is usually inconsequential but when this happens in science, then the opportunity to discover something new and potentially exciting is lost. History has just repeated itself when the Haass lab reported previously unrecognized proteolytic cleavages of the amyloid precursor protein (APP) that generate fragments intermediate in size between full length APP and C-terminal fragments (CTFs), the latter being precursors to the Aβ peptide [1]. With the attention given to the pathways of APP processing and Aβ production, it is almost shocking that this newly reported processing pathway has been uniformly ignored by the research community collectively for the past 25 years, even though the fragments are readily detected by western blotting.…”
Section: Npgmentioning
confidence: 99%
See 1 more Smart Citation